The New Product Portfolio Innovativeness–Stock Returns Relationship: The Role of Large Individual Investors' Culture. (November 2018) - Cillo, Paola; Griffith, David A.; Rubera, Gaia
The marketing–finance interface literature has investigated the direct link between innovativeness and stock returns. The authors extend this research by focusing on two open questions: How and under what conditions is innovativeness associated with stock returns? Answering these questions is important for managers who have to defend innovation investments to board members and time the introductions of new products. The authors investigate large individual investors and their national culture in the food and beverage industry. Combining multiple data sets, they first examine the relationship between innovativeness and large individual investors' stock holding decisions (i.e., to sell, hold onto, or buy a firm's stocks). The results indicate that national culture moderates this relationship. At the firm level, the authors show that large investors' stock holding partially mediates the innovativeness–stock returns relationship and that the culture of a firm's large investors moderates this mediated relationship. Thus, they unveil a special segment of investors, large individual investors, who influence the extent to which firms benefit from innovativeness in the stock market in the food and beverage industry.